Alteration of peripheral cortisol and autism spectrum disorder: A meta-analysis - Gao, Junwei; Zou, Jiao; Yang, Ling; Zhao, Jinghui; Wang, Lian; Liu, Tianyao; Fan, Xiaotang (Frontiers in Psychiatry, 2022)
Cortisol is the main HPA axis hormone secreted by the adrenal cortex, and influences metabolism, cognition, and behavior. Recently, a plethora of studies have tried to confirm the correlation between peripheral cortisol and autism spectrum disorder (ASD). However, the results were controversial. We assessed the effects of peripheral cortisol on ASD in this study. The included studies were identified according to the inclusion and exclusion criteria. The pooled Hedges’ g and its 95% confidence interval were selected to evaluate the association between peripheral cortisol and ASD. Subgroup analyses, sensitivity analyses, meta-regression, and publication bias tests were also undertaken based on the obtained information. There were a total of twelve studies with 375 ASD patients and 335 controls included in our meta-analysis. Obvious heterogeneity across studies was found in the overall analysis. Peripheral cortisol levels were significantly elevated in ASD patients compared with controls in the absence of obvious heterogeneity. A single study did not influence the overall comparison results. Meta-regression analyses revealed that age and gender of the included subjects, sample size, and publication year did not moderate effects on the present results. These findings may provide us some targeted strategies to the diagnosis and treatment of ASD.